Twenty Years of “Growth, Jobs And Investments” Strategy in the European Union– Macroeconomic Developments After the Maastricht Treaty - Jari Kaivo-oja; Teemu Haukioja; Ari Karppinen (Kaunas University of Technology, 2022)
Since the creation of the EU, its focal economic objective has been to achieve economic growth and
improved employment. The European Union’s present ’Growth, Jobs and Investments’ –strategy (GJI)
is a recent attempt to promote these goals. Since the global economic and financial crisis the EU has
been suffering from low level of investments. The purpose of this study is to assess the development of
growth, employment, and investments in the Member States from 1995 to 2015. For this purpose, a relatively
simple ‘GEI-index’ is developed. This aggregate index is a composition of indicators in GJI, which
in general evolve in the same direction. The study provides: (1) a comparative evaluation of the haves and
losers among the EU countries and (2) an empirical summary for the main objectives in the GJI-strategy.
The primary methods used are based on the GEI indicator and data-analyses. The key findings of the
study are: First, there seems to be some catching up concerning new member states that joined in the
EU in the 2000s. Second, during the whole period from 1995 to the beginning of the financial crisis all the
EU-28 countries – including the late members – show a positive development in the GEI-index. However,
from 2009 to 2015 seven countries – all of which belong into the euro area –had declining GEI-index.
These same countries had low level of investments and long lasting economic recession. Third, all the
other EU-28 countries, but except Greece, had positive development in the GEI-index in 2015 as compared
to the previous year. Obviously, our GEI-analyses cannot give a straight answer about the success
of the EU’s GJI-strategy as such. However, we see that our GEI-index provides a simple but effective
tool for the practical assessments of the EU’s growth policies. It is easy to interpret and visualize. Based
on our illustration of the GEI-index, we recommend that there is a serious need to re-evaluate the EU’s
growth strategies and economic policies concerning the employment and investments.